2-Methylimidazolium tetrakis(2-thenoyltrifluoroacetonato-κ2O,O′)neodymium(III) - José Manuel Bravo-Arredondo; Sylvain Bernès; Karen Mejía; Bertin Anzaldo; Erick Ramírez; David Moro (IUCrData)
The title complex, (C4H7N2)[Nd(C8H4F3O2S)4], is a salt formed via the acid–base reaction between 2-thenoyltrifluoroacetone (HTTA) and 2-methylimidazole (MeIm) in presence of neodymium(III) trifluoromethanesulfonate. The resulting compound features [Nd(TTA)4]− anions with the central rare-earth metal cation placed on a twofold rotation axis, and [MeImH]+ cations, disordered over an inversion centre. Cations and anions are linked through N—H...O hydrogen bonds to form zigzag chains running along [001].